2007
DOI: 10.1097/brs.0b013e31815588ed
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Magnetic Resonance Imaging of the Cervical Spine Using the NeuroSwing System

Abstract: Real-time dynamic examination of the cervical spine might be a useful supplement to the conventional static examination and may allow a more precise allocation of symptoms in some patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0
2

Year Published

2008
2008
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 10 publications
1
7
0
2
Order By: Relevance
“…They did not report whether dynamic MRI correlates with patient symptomatology any better than standard imaging. At least one commercial positioning device has been developed to facilitate these investigations, allowing an average of 42 u of flexion and 47 u of extension to be obtained [22]. Yoo et al [23] suggested that physiological narrowing of the exit foramina in extension may also be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…They did not report whether dynamic MRI correlates with patient symptomatology any better than standard imaging. At least one commercial positioning device has been developed to facilitate these investigations, allowing an average of 42 u of flexion and 47 u of extension to be obtained [22]. Yoo et al [23] suggested that physiological narrowing of the exit foramina in extension may also be demonstrated.…”
Section: Discussionmentioning
confidence: 99%
“…2,[7][8][9][10][11] It may also help in understanding the true nature of spinal pathologies. In addition, it can demonstrate the mobility of each motion segment and finally, relate the mobility to the changes in sagittal alignment and disc degeneration.…”
mentioning
confidence: 99%
“…Our data obtained by measuring the mentioned parameters and angles may help in assessing the cervical cord and brain stem positions and movements in certain disorders, diseases and traumatic injures of the cervical spine [5,11,12,17,18,21,23,[29][30][31][32][33][34][35]38]. This is especially true for the corresponding spine and CVJ degenerative diseases [2, 6,21,26,38].…”
Section: Discussionmentioning
confidence: 99%